Atopic Dermatitis: Research and Clinical Updates and Perspectives - Gregoriou, Stamatis (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue on Atopic Dermatitis focuses on novel insights into the pathogenesis of the immunological components of the disorder and the impaired epidermal barrier properties. It also explores the efficacy and safety of breakthrough therapies with topical agents and systemic therapies, such as monoclonals and JAK inhibitors. The aim of this Special Issue is also to present the expected future forefront of research and the treatment options that are expected to be available in the next few years.